Turkish primary school teachers' views on taking initiative during the teaching process - Akpinar, B.; Guner H.; Dogan Y. (My University, 2012)
This study aims to determine the primary-school teachers' views on taking initiative during the teaching process. To this end, a relevant scale has been conducted to a total number of 452 primaryschool teachers working in various cities in Turkey. The collected data have been analyzed by use of such statistical tests as arithmetic mean, Standard deviation, analysis of variance (Anova), independent t-test, KWH and MWU. According to the findings, it has been identified that the teachers, during the teaching process, use the teachers' guide-books prepared by the Ministry of Education rather than taking initiatives. However, while the teachers think that these ready-made materials restrict themselves, they do not seem to be complaining about using these materials. Another important find of the study is that younger teachers tend to take more initiatives. © Sila Science. All rights reserved.
Keywords: Teachers' guide-books; Teachers' initiative; Teachers' views